Peran PERAN CORPORATE GOVERNANCE DI IDX ESG LEADERS: - Adzra, Rifda Shabrina; Pertiwi, Tri Kartika (Universitas KH. Abdul Chalim Mojokerto, 2026)
The main aim of this analysis is to examine how corporate governance alter the effect of financial performance and debt on stock prices. Secondary sources, such as documents and literary evaluations, were used to collect the information that was acquired. The population of this study is comprised of businesses that have been designated as IDX ESG Leaders for the period of time spanning from 2020 to 2024. By using a method known as purposive sampling, we were able to choose 17 out of thirty organisations to serve as our sample, which resulted in the collection of 85 data points for the research. Moderated Regression Analysis (MRA) was used for the analysis this time. On the basis of the findings, it was determined that the stock prices of IDX ESG Leaders were significantly impacted by financial performance and leverage between the years 2020 and 2024. As a result of corporate governance, the stock prices of companies that are included on the IDX ESG Leaders list will be significantly influenced by the financial performance and leverage of these companies throughout the years 2020–2024. Keywords: Corporate Governance, Financial Performance, Leverage, Stock Price